Evaluating the persuasive communication techniques on Network Marketing a case study on NU Skin Philippines Enterprises Inc. - Naidas, Karina R.
In the Philippines today, network marketing businesses are are spreading like wild fire. Top Multilevel Network Marketing Companies to some unregistered, illegal Network Marketing Business, some Filipinos go crazy engaging in this kind of business. But because some of the Network Marketing business controversies such as some being a fraud, legal network marketers find it hard to convince people to join their companies. For a network marketing business to be successful, members of network marketers should learn how to persuade people. Hence, it is important for the researcher to evaluate the persuasive communicative strategies of one of the top network marketing business here in the Philippines ? Nu Skin Philippines Enterprises Inc. This research will analyze the speaker of Nu Skin and will be using Aristotle's Rhetoric, especially the Ethos, Logos, and Pathos. Aristotle's Rhetoric is used to analyze the speaker and the visual presentation's effectiveness when it comes to persuasion. Further, the speaker's organization of the information relayed to the audience was analyzed using Monroe's Motivated Sequence. After analyzing the gathered data, the researcher found out that the speaker was able to achieve the three means of persuasion according to Aristotle as well as the speaker was able to follow Monroe's Motivated Sequence making her an effective persuasive speaker. Even with the several studies conducted about persuasive communication strategies, this study will provide additional information also in a different context: Network Marketing context. Specially how Aristotle's Rhetoric and Monroe's Motivated Sequence will be used to analyze the effectiveness of the speaker
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication